Application and Evaluation of the Flipped Classroom Based on Micro-Video Class in Pharmacology Teaching - Wu, Yi-Ying; Liu, Sha; Man, Qiong; Luo, Feng-Lin; Zheng, Ya-Xin; Yang, Sheng; Ming, Xin; Zhang, Fang-Yan (Frontiers in Public Health, 2022)
With the continuous development of information technology, new teaching resources "micro-video class" and teaching model "flipped classroom" have gradually attracted the attention of teachers. Whether and how they can be applied in pharmacology teaching has already become the focus of medical education research in recent years. This paper explores the application and evaluation of the flipped classroom based on micro-video class in pharmacology teaching in our college. Students in Class 1 and Class 2 majoring in clinical medicine of 2018 in Chengdu Medical College were randomly divided into experimental group and control group. The teaching model of flipped classroom based on micro-video class was used in the experimental group, while the traditional teaching model was used in the control group. Theory tests and questionnaires were carried out at the end of the course. The average scores of theoretical knowledge in experimental group were significantly higher than those in control group (P < 0.05). In addition, the results of the feedback questionnaire showed that the overall satisfaction of students participating in flipped classroom based on micro-video class was higher (P < 0.05), and students thought that their learning enthusiasm, learning efficiency, and abilities of autonomous learning and problem-solving were greatly improved compared with those of students taught applying the traditional teaching model. Flipped classroom based on micro-video class model successfully improved the outcome of pharmacology teaching. It is supposed to provide reference for the reform of pharmacology teaching in medical college.